Illegal wildlife trade and the persistence of “plant blindness” - Margulies, J; Bullough, L; Hinsley, A; Ingram, D; Cowell, C; Goettsch, B; Klitgård, B; Lavorgna, A; Sinovas, P; Phelps, J (Wiley, 2019)
This review investigates the ways in which “plant blindness,” first described by Wandersee and Schussler (1999, p. 82) as “the misguided anthropocentric ranking of plants as inferior to animals,” intersects with the contemporary boom in research and policy on illegal wildlife trade (IWT). We argue that plants have been largely ignored within this emerging conservation arena, with serious and detrimental effects for biodiversity conservation. With the exception of the illegal trade in timber, we show that plants are absent from much emerging scholarship, and receive scant attention by US and UK funding agencies often driving global efforts to address illegal wildlife trade, despite the high levels of threat many plants face. Our article concludes by discussing current challenges posed by plant blindness in IWT policy and research, but also suggests reasons for cautious optimism in addressing this critical issue for plant conservation.